Photovoltaic Solar Technologies: Solution to Affordable, Sustainable, and Reliable Energy Access for All in Rwanda - Samuel Bimenyimana; Godwin Norense Osarumwense Asemota; Jean De Dieu Niyonteze; Cyprien Nsengimana; Paula Jeanne Ihirwe; Lingling Li (International Journal of Photoenergy)
Despite remarkable economic growth and development in recent decades, Rwanda has been still facing energy crises and challenges. Although the country has considerable energy assets, less than 10% is utilized for its local electricity needs. Currently, national installed generation capacity is estimated at 221 MW, for a population around 12 million, and electricity access is estimated at 51% (37% grid and 14% off-grid networks). About half the population is without electricity access while the grid-connected users face high electricity tariffs and frequent power outages (blackouts). The national grid itself is also experiencing high losses. This paper used the HOMER software for modeling the optimal, sustainable, reliable, and affordable photovoltaic solar technologies as energy solutions for all (off-grid and on-grid users) in Rwanda. The selection and recommendation of a suitable photovoltaic (PV) solar technology depend on its annual electricity production capacity, electrical load, renewable energy penetration percentage, economic viability, feasibility, affordability, carbon footprint, and greenhouse gas emission level for climate change considerations towards a clean and greener future. The results show that the least cost of energy (LCOE) for electricity production by each of the solar PV systems with storage, PV-grid-connected household, and PV-grid connection with storage was 67.5%, 56.8%, and 33.9%, respectively, lower than the normal electricity tariff in Rwanda. The PV systems with storage proposed in this paper could be effective in increasing national energy resource exploitation, providing affordable and reliable energy access to all citizens.